Islam and Indonesian Political Literacy: Religious Approach to Political Education in Sambas Regency - Mualimin, Mualimin; Rofii, Rofii; El Bilad, Cecep Zakarias; Fathiyakan, Fathiyakan; Ariska, Ariska (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This article aims to analyze political education using a religious approach conducted by election organizers in Sambas Regency. This study is a qualitative research with a phenomenological approach, with the locus of the study is the General Election Commission (KPU) and the General Election Supervisory Agency (Bawaslu) of Sambas Regency. Data was collected from March to June 2022 through participative observation and in-depth interviews. The informants in this study amounted to six people. The data obtained were then analyzed using the Miles and Huberman model interactive qualitative analysis technique, namely data reduction, data display, and conclusion. Data analysis shows that using a religious approach in political education is inseparable from the socio-religious background of the Sambas Regency society, which is mostly Malay, where Islam plays a significant role in the life of the Sambas Malay people. Implementing political education is by engaging religious institutions in various political education programs. The engagement of religious institutions is based on the argument that they are opinion leaders of Muslims and have a better understanding of the proper religious narratives in explaining elections and politics to the religious society. Political education with a religious approach is also carried out by utilizing Muslim religious celebrations and ceremonies to socialize politics and elections in society. Based on these findings, the conclusion is that religion not only plays a role in religiosity and spiritual life but is also consumed and commodified as a tool to enhance a society's political understanding and knowledge. Keywords: Religious Approach, Political literacy, Political Education, Sambas Regency, Malay